Attack on Titan. 25 - Isayama, Hajime, 1986- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"The final battle rages on between the Survey Corps and the genocidal Colossus and Armored Titans. It's a personal fight that has driven old friends to kill each other, with the fate of humanity and the truth behind the Titan threat in the balance"--Amazon.